2016
DOI: 10.1016/j.bonr.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Methionine restriction alters bone morphology and affects osteoblast differentiation

Abstract: Methionine restriction (MR) extends the lifespan of a wide variety of species, including rodents, drosophila, nematodes, and yeasts. MR has also been demonstrated to affect the overall growth of mice and rats. The objective of this study was to evaluate the effect of MR on bone structure in young and aged male and female C57BL/6J mice. This study indicated that MR affected the growth rates of males and young females, but not aged females. MR reduced volumetric bone mass density (vBMD) and bone mineral content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 60 publications
7
21
0
1
Order By: Relevance
“…Plasma markers for renal injury—for example, A2M, cystatin C, lipocalin 2, and clusterin—were reduced (Table 3; P < 0.05) in 5/6Nx MR mice compared with 5/6Nx CF mice. Consistent with other studies on MR mice (14, 17), 5/6Nx MR mice exhibited less weight gain than did 5/6Nx CF mice (Supplemental Fig. 2 C ; P < 0.001), despite increased food intake (Supplemental Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Plasma markers for renal injury—for example, A2M, cystatin C, lipocalin 2, and clusterin—were reduced (Table 3; P < 0.05) in 5/6Nx MR mice compared with 5/6Nx CF mice. Consistent with other studies on MR mice (14, 17), 5/6Nx MR mice exhibited less weight gain than did 5/6Nx CF mice (Supplemental Fig. 2 C ; P < 0.001), despite increased food intake (Supplemental Fig.…”
Section: Resultssupporting
confidence: 90%
“…We also measured known plasma markers that are affected by MR (Supplemental Table 3). Current data are consistent with our previous studies (14,17) in that FGF-21 and adiponectin were significantly elevated (P , 0.01 and P , 0.001, respectively), whereas IGF-1 and leptin levels were significantly reduced (P , 0.05 and P , 0.01, respectively) in UNx MR mice compared with UNx CF mice. Renal gene expression for selected ion transporter genes indicated upregulation of the markers, Aqp2, Slc12a1, Scnn1a, Slc26a4, and Slc6a19, in UNx MR mice compared with UNx CF mice ( Fig.…”
Section: Altered Renal Response Of Unx Mice On Mrsupporting
confidence: 92%
“…Effects of MR on growth rates and food intake in both young and adult mice were similar to those previously observed in rodents [20]. Young mice on the CD continued to grow until the end of the study; those on MR also continued to grow but at a slower rate (Figure 1).…”
Section: Resultssupporting
confidence: 81%
“…In the nano‐indentation measurements performed on the surfaces of vertebrate bodies, ovariectomized rats that were fed a PR‐diet exhibited a lower tissue elastic modulus, hardness, and energy dissipation compared to those of the sham group, and a 5% essential amino acid supplement reversed this loss in intrinsic strength . However, under isoprotein conditions, our research team found that specific restrictions in dietary methionine did not change the intrinsic material properties that were measured by nano‐indentation in young and adult mice of both genders (Ouattara et al ., unpublished) . More studies that use this novel material testing system to explore the effects of dietary restrictions on the skeleton are definitely required.…”
Section: Diet Restrictions and Bone Qualitymentioning
confidence: 99%
“…147 However, under isoprotein conditions, our research team found that specific restrictions in dietary methionine did not change the intrinsic material properties that were measured by nano-indentation in young and adult mice of both genders (Ouattara et al, unpublished). 148 More studies that use this novel material testing system to explore the effects of dietary restrictions on the skeleton are definitely required.…”
Section: Viewpoints From Energy Metabolism Growth/aging and Bone Qumentioning
confidence: 99%